Antisense Expression of the CK2 α-Subunit Gene in Arabidopsis. Effects on Light-Regulated Gene Expression and Plant Growth - Yew Lee; Lloyd, Alan M.; Roux, Stanley J. (Plant physiology (Bethesda), 1999)
The protein kinase CK2 (formerly casein kinase II) is thought to be involved in light-regulated gene expression in plants because of its ability to phosphorylate transcription factors that bind to the promoter regions of light-regulated genes in vitro. To address this possibility in vivo and to learn more about the potential physiological roles of CK2 in plants, we transformed Arabidopsis with an antisense construct of the CK2 α-subunit gene and investigated both morphological and molecular phenotypes. Antisense transformants had a smaller adult leaf size and showed increased expression of chs in darkness and of cab and rbcS after red-light treatment. The latter molecular phenotype implied that CK2 might serve as one of several negative and quantitative effectors in light-regulated gene expression. The possible mechanism of CK2 action and its involvement in the phytochrome signal transduction pathway are discussed.